2021
DOI: 10.21203/rs.3.rs-1039705/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Process Evaluation of ‘We Can Quit’: a Community-Based Smoking Cessation Intervention Targeting Women From Areas of Socio-Disadvantage in Ireland

Abstract: Background: Smoking poses a serious risk of early preventable death and disease especially for women living with socio-economic disadvantage (SED). A smoking cessation programme ‘We Can Quit’ was developed in Ireland tailored to SED women. The programme includes group-based support delivered by trained lay local women and free nicotine replacement therapy (NRT). The intervention was pilot tested in a cluster randomised controlled trial, ‘We Can Quit 2’. A process evaluation assessed feasibility and acceptabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…The overall aim of WCQ2 was to determine the feasibility and acceptability of trial-related processes and of the WCQ intervention. A description of the trial protocol [ 18 ] and trial findings can be found elsewhere [ 19 , 34 ]. In brief, the pilot trial was conducted in four consecutive phases (waves), each one taking place in a randomly allocated matched pair of SED districts in Ireland [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The overall aim of WCQ2 was to determine the feasibility and acceptability of trial-related processes and of the WCQ intervention. A description of the trial protocol [ 18 ] and trial findings can be found elsewhere [ 19 , 34 ]. In brief, the pilot trial was conducted in four consecutive phases (waves), each one taking place in a randomly allocated matched pair of SED districts in Ireland [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The type, duration and intensity of interventions varied greatly between studies. Interventions consisted, for example, (both solely or combined) of classes or workshops (e.g., Dickin et al, 2014;Hand et al, 2014;Nieves et al, 2022), policy implementations (e.g., tobacco price increases or sugar-content-based taxes; Essman et al, 2021;Kim & Cho, 2022;Tabuchi et al, 2017), cognitive or behavioral counselling (e.g., Jenum et al, 2009;Steptoe et al, 2004), therapy (e.g., pharmacotherapy, cognitive behavioral therapy or nicotine replacement therapy; Darker et al, 2022;Landais et al, 2021;Webb Hooper et al, 2017) or environmental changes (e.g., nudges or neighborhood walking route; Huitink et al, 2020;Prins et al, 2019). Most interventions had a relatively short duration of one occasion up to two months and interventions differed in the number of contact moments provided (e.g., 6week interventions consisting of weekly one-hour education classes versus sessions of 15 hours in total; Backman et al, 2011;West et al, 2020).…”
Section: Intervention Characteristicsmentioning
confidence: 99%